The Power to Nudge. Issue 2 (19th April 2017) - SCHMIDT, ANDREAS T.
Abstract : Nudging policies rely on behavioral science to improve people's decisions through small changes in the environments within which people make choices. This article first seeks to rebut a prominent objection to this approach: furnishing governments with the power to nudge leads to relations of alien control, that is, relations in which some people can impose their will on others—a concern which resonates with republican, Kantian, and Rousseauvian theories of freedom and relational theories of autonomy. I respond that alien control can be avoided, if nudging is suitably transparent and democratically controlled. Moreover, such transparency and democratic control are institutionally feasible. Building on this response, I then provide a novel and surprising argument for more nudging: democratically controlled public policy nudging can often contain the power of private companies to nudge in uncontrolled and opaque ways. Therefore, reducing alien control often requires more rather than less nudging in public policy.